Upaya Peningkatan Kemampuan Membaca Permulaan Siswa Kelas I SD dengan Metode Mueller - Masnur Muslich (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: Based on preelimenary observation it can found early reading competencies of first class students of SDN Leminggir I were low. Based on the facts, researcher conducted improvement through Mueller method, i.e. using concrete things around children in the game activities context. The purpose of the research was to improve early reading competencies of first class students of I SDN Leminggir I. Results found there were improvement early reading competencies of first class students with mean 12,5%. Compared with school’s standard (85%), evaluation results of second cycle, mastery learning achievement 90%.